Synthesis and Characterization of Molybdenum Phthalocyanine as Target Material for High Specific Activity Molybdenum-99 Production - Muhamad Basit Febrian; Duyeh Setiawan; Hilda Hidayati (Universitas Gadjah Mada, 2019)
High specific activity is a necessity in the fabrication of 99Mo/99mTc radioisotope generators. Recoil reaction, or the Szilard-Chalmers effect, is a method that could be used as an alternative method for increasing specific activity in radioisotope production in light of tightening regulation of highly enriched uranium (HEU) irradiation. Phthalocyanine compounds are usually used as the target material in recoil reactions for the production of high specific radioisotope activity via the (n,γ) reaction. Molybdenum phthalocyanine (Mo-Pc) could be a promising target material in recoil reactions for producing high specific activity of 99Mo. Mo-Pc was synthesized via solid-state reaction between ammonium heptamolybdate and phthalonitrile in a reflux system at 300 °C for 3 h. This optimum condition was identified after performing several variations of temperature and time of reaction, considering FTIR spectra, the yield of product and melting point of the product. XRD measurement showed that Mo-Pc synthesized at optimum condition was free from MoO2, phthalimide and unreacted molybdenum. Mo-Pc has UV-vis properties of Q-band absorption between 600 and 750 nm when dissolved in tetrahydrofuran, dimethylformamide and trifluoroacetic acid. Splitting at absorption peak in tetrahydrofuran and dimethylformamide solution indicated that protonation had occurred. This split peak did not appear in a trifluoroacetic acid solution. In the preliminary study of irradiation of 1 g Mo-Pc at 3.5x1012 n cm–2 s–1 neutron flux, followed by dissolution in tetrahydrofuran and extraction of Mo-99 into NaOH, we obtained Mo-99 solution with a specific activity of 682.35 mCi/g Mo, this being 254.61 times higher than in the regular MoO3 target.